How to measure teamwork and networking competencies - Juan A. Marin-Garcia; Maribel Martínez Villaescusa; Tomás Bonavía (WPOM : Working Papers on Operations Management, 2019)
Our aim is present a protocol to develop a measurement questionnaire that allows a valid and reliable self-evaluation of the transversal competencies related to team work (TW) and networking (NW). It will be design to evaluate these competences among professionals from different organizations or job applicants. In this paper, we will focus on how to filter a bank of behavioral items, verifying that the items finally analysed: a) Represent one or several conceptual dimensions within TW or NW. b) Ensure the inter-agreement between independent evaluators to analyze the overlap between items and dimensions, and be able to classify the items in the correct dimension.c) Check that the set of items retained by agreement between evaluators represent all the subdimensions of team work and networking.